European hare invasion in southeastern Brazil: identifying drivers of occupancy and abundance and analyzing the invader\'s impact on the Brazilian cottontails spatial distribution - Salvador, Nielson Aparecido Pasqualotto (2023)
Non-native species invasion is a major driver of biodiversity loss. In South America, European hare (Lepus europaeus() was introduced in the late 19th in central Argentina and Chile and rapidly expanded its distribution northwards, likely reaching southeastern Brazil during the last decade. Despite the significant environmental damage that European hare has caused to recipient communities worldwide, little attention has been given to uncover the main drivers of this non-native species occupancy and local abundance in the Neotropics, and the influence of this non- native hare on the Brazilian cottontail probability of using native Neotropical habitats in southeastern Brazil. In this doctoral thesis, I used two data sets obtained from agriculturally dominated landscapes of southeastern Brazil to investigate i) the main occupancy drivers of the European hare, assessing support for the disturbance and biotic resistance hypotheses (Chapter I); ii) the relative importance of spatial (compositional and configurational) and temporal heterogeneity compared to the amount of land cover types as predictors of the European hare local abundance (Chapter II); and iii) the influence of the presence of European hares and the proximity of farmhouses on the habitat of the Brazilian cottontail from southeastern Brazil (Sylvilagus minensis). The two datasets were designed to provide 1) similar sampling effort among areas dominated by native habitats (inside protected areas) and areas where agricultural lands and native habitats coexist (outside protected areas) and relative large sample size (n=205) in a more geographically restricted area (> 0.03 Mha; dataset 1); and 2) a more comprehensive sampling of sites (n=55) embedded in agricultural dominated landscapes located in a much wider area (> 3Mha; dataset 2). I used occupancy modeling to investigate a priori my defined hypotheses while explicitly accounting for detection errors. The main findings indicated that i) European hare occupancy is mainly driven by the niche opportunities created by human-disturbed habitats; biotic resistance plays a secondary role and likely only due to native forest, ii) local abundance of European hare was high in areas with high diversity of land cover types, including sugarcane but no savanna and species abundance estimates were low and did not vary dramatically among sites suggesting this non-native species have not yet attained high local density in our study area; and iii) the Brazilian cottontail is more likely to use sites predominantly covered by native forest and away from farmhouses, regardless of the European hare presence, suggesting that these two species are spatially segregating due to different habitat preferences rather than European hare competitively excluding the native cottontail. Collectively, these findings improve our understanding of the success of the European hare invasion in the Neotropics, and also provide valuable insights into the interaction of the European hare with a native cottontail and future of this invasion process in South America.